Emotional intelligence in the structure of self-control among junior athletes - Popovych, I.; Danko, D.; Yakovleva, S.; Haponenko, L.; Shcherbyna, O.; Kryzhanovskyi, O.; Hoian, I. (Journal of Physical Education and Sport, 2025)
The aim of this study is to empirically investigate and theoretically substantiate the role of emotional intelligence (EQ) within the self-control structure of junior athletes. Methods: The sample consisted of 184 junior athletes from both team sports (football and handball) and individual sports (track and field, artistic gymnastics, freestyle wrestling, weightlifting, and boxing). These athletes were students at sports schools for children and youth and were part of professional football and handball clubs competing in the national championship. The descriptive frequency characteristics of the respondents` ages are as follows: M = 16.96; SD = ±3.37; Me = 17.00. The parameters of emotional intelligence, volitional control, and subjective control were assessed using psycho-diagnostic tools that were valid, reliable, and specifically adapted for sports samples. Results: The empirical data followed a normal distribution, allowing the use of Pearson`s correlation coefficient (R) to identify fourteen direct correlations and two inverse correlations (p <= .050; p <= .010; p = .000). It was found that the most dependent parameter of emotional intelligence was "self-control and self-regulation of emotions", which showed the highest number of correlations (seven) and the strongest associations at significant levels (p <= .001; p = .000). The profile of junior athletes` overall self-control enabled a visual comparison of the key dimensions of self-control. It was explained that the technical component, latent mental resources, and psychological literacy give juniors an advantage at the final stage when all the strong and equal athletes have reached the final competitions. There is a caveat that demonstrating a high level of perseverance does not allow respondents to consider others` emotions, i. e. the desire to win at any cost blocks the defense mechanisms of emotional intelligence. This is a dangerous and uncontrolled state that borders on the affective state and can have detrimental consequences for junior athletes. Discussion and conclusions. It was substantiated that the research into emotional intelligence in the structure of junior athletes` volitional control is a successful attempt to establish correlations between the parameters of the examined phenomena applying relevant psycho-diagnostic methodologies, sensitive to critical periods in the formation of a junior athlete`s personality, the development of worldviews, and age-related patterns of psychophysiological processes. There was a caveat that low values of the parameter "self-control of an athlete`s health and disease" can pose a latent danger, especially in team sports, where the absence of key players can have a considerable impact on the tactical organization of the game. It is recommended that the established scientific facts about the dimensions of EQ and the parameters of volitional control be implemented in work with juniors in all learning, training, competitive, and rehabilitative activities.